Crystalline Nanoporous Materials Based on Poly(2, 6‐dimethyl‐1, 4‐phenylene)oxide. Issue 1 (January 2014) - Daniel, Christophe; Longo, Simona; Galizia, Michele; Bulavin, Leonid; Guenet, Jean‐Michel
Summary Different types of crystalline nanoporous materials (powders, films, aerogels) based on poly(2, 6‐dimethyl‐1, 4‐phenylene)oxide can be easily obtained depending on the preparation procedures. The nanoporous nature of the crystalline phase confers to these materials peculiar transport properties which make them particularly interesting for a potential use as a sorption medium to remove traces of pollutants from water and air or for membrane based gas separation processes. Different aspects relative to the structure and the transport properties of these new polymeric materials are described.